(untitled) (CIPEEX, 2022)
Non-Olympic sports modalities like Crossfit® are growing in numbers of practitioners, and although not all participants seek competitive athleticism, everyone aims to improve performance at elevated recreational levels [1]. Therefore, ergogenic resources in general are targeted by recreational and competitive practitioners of functional fitness, as well as in other modalities. It is then articulated that athletic performance can be lawfully influenced by the effects of the application or ingestion of menthol-flavored refreshing substances (Menthol) directly in the oral cavity, through rinsing or gargling, or by proper ingestion [2-4]. This technique had already been applied in previous studies with carbohydrates and caffeine, showing significant results [5]. So, when we analyze performance from the specific perspective of functional fitness, along with different manifestations of strength, the available data on the use of menthol as a performance-enhancing substance is still scarce, warranting further investigation.